Postnatal Gut Immunity and Microbiota Development Is Minimally Affected by Prenatal Inflammation in Preterm Pigs - Pan, Xiaoyu; Zhang, Du; Nguyen, Duc Ninh; Wei, Wei; Yu, Xinxin; Gao, Fei; Sangild, Per T. (Frontiers in Immunology, 2020)
Chorioamnionitis (CA), resulting from intra-amniotic inflammation, is a frequent cause of preterm birth and exposes the immature intestine to bacterial toxins and/or inflammatory mediators before birth via fetal swallowing. This may affect intestinal immune development, interacting with the effects of enteral feeding and gut microbiota colonization just after birth. Using preterm pigs as model for preterm infants, we hypothesized that prenatal exposure to gram-negative endotoxin influences postnatal bacterial colonization and gut immune development. Pig fetuses were given intra-amniotic lipopolysaccharide (LPS) 3 d before preterm delivery by cesarean section, and were compared with litter-mate controls (CON) at birth and after 5 d of formula feeding and spontaneous bacterial colonization. Amniotic fluid was collected for analysis of leukocyte counts and cytokines, and the distal small intestine was analyzed for endotoxin level, morphology and immune cell counts. Intestinal gene expression and microbiota were analyzed by transcriptomics and metagenomics, respectively. At birth, LPS-exposed pigs showed higher intestinal endotoxin, neutrophil/macrophage density and shorter villi. About 1.0% of intestinal genes were affected at birth and DMBT1, a regulator of mucosal immune defense, was identified as the hub gene in the co-expression network. Genes related to innate immune response (TLR2, LBP, CD14, C3, SFTPD), neutrophil chemotaxis (C5AR1, CSF3R, CCL5) and antigen processing (MHC II genes and CD4) were also affected and expression levels correlated with intestinal neutrophil/macrophage density and amniotic fluid cytokine levels. On day 5, LPS and CON pigs showed similar sensitivity to necrotizing enterocolitis (NEC), endotoxin levels, morphology, immune cell counts, gene expressions and microbiota composition (except for difference in some low-abundant species). Our results show that CA markedly affects intestinal genes at preterm birth, including genes related to immune cell infiltration. However, a few days later, following the physiological adaptations to preterm birth, CA had limited effects on intestinal structure, function, gene expression, bacterial colonization and NEC sensitivity. We conclude that short-term, prenatal intra-amniotic inflammation is unlikely to exert marked effects on intestinal immune development in preterm neonates beyond the immediate neonatal period.